Association of oxidative balance score with chronic kidney disease: NHANES 1999-2018 - Wen, Haibin; Li, Xianhua; Chen, Jiangming; Li, Yi; Yang, Nailong; Tan, Ning (Frontiers in Endocrinology, 2024)
Background: The Oxidative Balance Score (OBS), which quantifies the balance between antioxidants and pro-oxidants influenced by diet and lifestyle, is crucial given oxidative stress's significant role in Chronic Kidney Disease (CKD). This study aims to determine the association between OBS and CKD using data from the National Health and Nutrition Examination Survey (NHANES) 1999-2018. Methods: We analyzed data from the National Health and Nutrition Examination Survey (NHANES) spanning 1999 to 2018. OBS was constructed from a detailed array of 20 factors, including dietary nutrients and lifestyle behaviors. The relationship between OBS and CKD risk was evaluated using weighted logistic regression models, adjusted for potential confounders, with a generalized additive model (GAM) examining non-linear associations. Subgroup analyses and interaction effects across diverse demographic and clinical groups, along with sensitivity analyses, were performed to validate the findings. Results: Among 32,120 participants analyzed, 4,786 were identified with CKD. Fully adjusted weighted logistic regression analysis revealed that each unit increase in OBS was associated with a 2% reduction in CKD prevalence [OR: 0.98 (0.98-0.99), P < 0.001]. Higher OBS quartiles were significantly correlated with a decreased CKD risk [Q4 vs. Q1: OR: 0.82 (0.68-0.98), P = 0.03; P for trend = 0.01]. The GAM and smoothed curve fit indicated a linear relationship between OBS and the risk of CKD. Stratified and sensitivity analyses further substantiated the inverse relationship between OBS and CKD prevalence. Conclusions: Our findings from the NHANES data affirm a significant inverse association between OBS and CKD risk in the U.S. population, underscoring the role of optimizing dietary and lifestyle factors in managing CKD risk.These results advocate for incorporating OBS considerations into CKD prevention and treatment strategies.